The Influence of Machiavellianism, Love of Money and Internal Control on the Tendency of Asset Misuse in Government-Owned Enterprises XYZ in Semarang - Farlina Wahyu Listyo; Nur Cahyonowati (UNIB Press, 2022)
This paper aims to investigate the effect of Machiavellianism, love of money, and internal control on the tendency of asset misuses in the workplace, especially in the state-owned company XYZ in Semarang. This study used survey method to collect data from employees of a state-owned company in Semarang City. The data consisted of 161 questionnaires which were analyzed using WarpPLS 7.0. The finding showed that Machiavellianism, love of money, have a significant positive effect on the tendency of asset misuses in BUMN companies, while internal control has a significant negative effect on the tendency of asset misuses in BUMN companies. This finding implies the importance of considerations in psychological aspects when it comes to fraud prevention. Additionally, the finding implies that the internal control is a mandatory mechanism in the company's managerial activities for fraud prevention.Keywords: Machiavellianism, Love of Money, Internal Control Misappropriate Assets, Government-Owned Enterprises.